Fungal species isolated from Quercus castaneifolia in Hyrcanian Forests, North of Iran - MOHAMMAD REZA KAVOSI; FERIDON FARIDI; GOODARZ HAJIZADEH (Society for Indonesian Biodiversity, 2013)
Kavosi MR, Feridon F, Hajizadeh G. 2013. Fungal species isolated from Quercus castaneifolia in Hyrcanian Forests, North of Iran. Biodiversitas 14: 61-66. In order to isolate and identify of fungi associated with Quercus castaneifolia seed, sampling carried out in Shast-Kalate, Ghorogh, Loveh and Golestan forest. Collected seeds sterilized and then separated sections including: outer section of seed (crust) and inner seed section (endosperm). Each section of seed tissue is cultured on potato dextrose agar media. After sub-culture and providing of the fungi pure cultures, various species isolated and identified by spores characteristics, their size and color, including: Aspergillus flavus, A. niger, Curvularia affinis, Trichoderma harzianum, Trichothecium roseum, Eurotium rubrum, E. amstelodami, Penicillium implicatum, P. fellutanum, Diplodia sp. Nigrospora gossypi, Alternaria alternata , Fusarium oxysporum and Beltrania santapaui. The most frequency of fungus in Shast-Kalate forest was P. implicatum by 74% of frequency within seed section, the most frequency in Ghorogh and Loveh Forest was P. fellutanum with 63 and 66% of frequency within seed section respectively and the most frequency in Golestan forest was B. santapaui by 51% of frequency outer seed section. The result showed diversity of the fungi on the outer seed section is higher than within seed section. The results also showed during several isolation a saprophyte fungus always could be finding on the acorn seeds. This is the comprehensive report on fungi associated with Quercus castaneifolia seed in Hyrcanian forest, North of Iran.